Potential application of mesenchymal stem cells and their exosomes in lung injury: an emerging therapeutic option for COVID-19 patients - Sara Al-Khawaga (4792761) (2020)
The COVID-19 pandemic has negatively impacted the global public health and the international economy; therefore, there is an urgent need for an effective therapy to treat COVID-19 patients. Mesenchymal stem cells (MSCs) have been proposed as an emerging therapeutic option for the SARS-CoV-2 infection. Recently, numerous clinical trials have been registered to examine the safety and efficacy of different types of MSCs and their exosomes for treating COVID-19 patients, with less published data on the mechanism of action. Although there is no approved effective therapy for COVID-19 as of yet, MSC therapies showed an improvement in the treatment of some COVID-19 patients. MSC’s therapeutic effect is displayed in their ability to reduce the cytokine storm, enhance alveolar fluid clearance, and promote epithelial and endothelial recovery; however, the safest and most effective route of MSC delivery remains unclear. The use of poorly characterized MSC products remains one of the most significant drawbacks of MSC-based therapy, which could theoretically promote the risk for thromboembolism. Optimizing the clinical-grade production of MSCs and establishing a consensus on registered clinical trials based on cell-product characterization and mode of delivery would aid in laying the foundation for a safe and effective therapy in COVID-19. In this review, we shed light on the mechanistic view of MSC therapeutic role based on preclinical and clinical studies on acute lung injury and ARDS; therefore, offering a unique correlation and applicability in COVID-19 patients. We further highlight the challenges and opportunities in the use of MSC-based therapy. Other Information Published in: Stem Cell Research & Therapy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s13287-020-01963-6